TYPES OF PESTS AND DISEASES WHICH ARE SPREAD IN THE BIOTOPE OF CUCURBIT SCROPS AND MEASURES TO CONTROL THEM - Risnazar Orazbaevich Yusupov,; Ispandiyar Kerimbergenovich Durshimbetov, (EPRA International Journal of Research and Development (IJRD), 2022)
In the article, the conditions of bioecological development of pest species, the dynamics of development during the vegetation period and the criterion of harmfulness, types of diseases are studied in the fields. Information on the biological effectiveness of measures on controlling pests and diseases encountered in the fields is given.